Rozwój makroekonomii a globalizacja - Noga, Marian (The development of macroeconomy in terms of globalisation., 2005)
A changeable research area of macroeconomy caused by a globalisation of the world economy is presented in the article. The author puts emphasis on stopping the disputes between the representatives of macroeconomy and searching for what they have in common. The following fields of agreement are indicated: 1. Approach of the real product to potentially maximum GDP. 2. Full employment. 3. Stabilization of the general level of prices. 4. Balanced development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 13-17